CONCEPTUAL BASES AND IMPLEMENTATION OF THE EU YOUTH POLICY - E. N. Grachev (Vestnik MGIMO-Universiteta)
Europe is making significant efforts to create a common space where not only common political institutions and values, but also common future is to be shaped. And it is young people who is selected to be the main policy object for building common European identity. To this end in recent years, the European Union has worked out the institutional mechanisms of its youth policy, has formed special agencies for its implementation, developed legal framework. The main document, which laid the conceptual basis of EU youth policy is the White Paper. The document determines the most challenging issues in youth policy that need to be resolved in the short and long term. The next major document - the European Youth Pact - has become a real legal act which came into force throughout the European Union. The most important document which determines the guidelines of the current EU youth policy is a strategy "Youth - Investing and Empowering." The strategy settles a key vector of European youth policy for all EU countries. All documents take into account the interests of the whole EU and not individual nation states that is why they influence young people at the supranational level. The European Union has developed a full-fledged system of management of youth policy on two levels: the supranational (pan-European) and national. Council of Europe and European Parliament are responsible for the implementation of youth policy at supranational level. Various national agencies are responsible for the implementation of certain EU youth programs at national level. The EU documents on the youth policy show that the youth is viewed by European politicians as one of the most politically important social groups in Europe. That is why youth policy is directed not only at youth development, but has to it a significant political component. A significant part of the youth policy is related to the involvement of young people in the democratic institutions, the involvement of young people in the EU governance.